The effect of rowing headgear on forced convective heat loss and radiant heat gain on a thermal manikin headform - Bogerd, C. P.; Brühwiler, P. A.; Heus, R. (Journal of Sports Sciences, 2008)
Both radiant and forced convective heat flow were measured for a prototype rowing headgear and white and black cotton caps. The measurements were performed on a thermal manikin headform at a wind speed of 4.0 m · s-1 (s = 0.1) in a climate chamber at 22.0°C (s = 0.05), with and without radiant heat flow from a heat lamp, coming from either directly above (90°) or from above at an angle of 55°. The effects of hair were studied by repeating selected measurements with a wig. All headgear reduced the radiant heat gain compared with the nude headform: about 80% for the caps and 95% for the prototype rowing headgear (P < 0.01). Forced convective heat loss was reduced more by the caps (36%) than by the prototype rowing headgear (9%) (P < 0.01). The radiant heat gain contributed maximally 13% to the net heat transfer, with or without headgear, showing that forced convective heat loss is the dominant heat transfer parameter under the chosen conditions. The results of the headgear - wig combinations were qualitatively similar, with lower absolute heat transfer.